# We've moved to http://drummondlab.org.

the drummond lab

## Introduction

Here I will treat some basic questions in population genetics. For personal reasons, I tend to include all the algebra.

## Per-generation and instantaneous growth rates

What is the relationship between per-generation growth rates and the Malthusian parameter, the instantaneous rate of growth?

Let $\displaystyle n_i(t)$ be the number of organisms of type $\displaystyle i$ at time $\displaystyle t$ , and let $\displaystyle R$ be the per-capita reproductive rate per generation. If $\displaystyle t$ counts generations, then

$\displaystyle n_i(t+1) = n_i(t)R\!$
and
$\displaystyle n_i(t) = n_i(0)R^t.\!$

Now we wish to move to the case where $\displaystyle t$ is continuous and real-valued. As before,

$\displaystyle n_i(t+1) = n_i(t)R\!$
but now
 $\displaystyle n_i(t+\Delta t)\!$ $\displaystyle =n_i(t)R^{\Delta t}\!$ $\displaystyle n_i(t+\Delta t) - n_i(t)\!$ $\displaystyle = n_i(t)R^{\Delta t} - n_i(t)\!$ $\displaystyle \frac{n_i(t+\Delta t) - n_i(t)}{\Delta t}$ $\displaystyle =\frac{n_i(t)R^{\Delta t} - n_i(t)}{\Delta t}$ $\displaystyle \frac{n_i(t+\Delta t) - n_i(t)}{\Delta t}$ $\displaystyle =n_i(t) \frac{R^{\Delta t} - 1}{\Delta t}$ $\displaystyle \lim_{\Delta t \to 0} \left[{n_i(t+\Delta t) - n_i(t) \over \Delta t}\right]$ $\displaystyle =\lim_{\Delta t \to 0} \left[ n_i(t) \frac{R^{\Delta t} - 1}{\Delta t}\right]$ $\displaystyle \frac{d n_i(t)}{dt}$ $\displaystyle =n_i(t) \lim_{\Delta t \to 0} \left[\frac{R^{\Delta t} - 1}{\Delta t}\right]$ $\displaystyle \frac{d n_i(t)}{dt}$ $\displaystyle =n_i(t) \ln R\!$

where the last simplification follows from L'Hôpital's rule. Explicitly, let $\displaystyle \epsilon=\Delta t$ . Then

 $\displaystyle \lim_{\Delta t \to 0} \left[{R^{\Delta t} - 1 \over \Delta t}\right]$ $\displaystyle = \lim_{\epsilon \to 0} \left[\frac{R^{\epsilon} - 1}{\epsilon}\right]$ $\displaystyle =\lim_{\epsilon \to 0} \left[\frac{\frac{d}{d\epsilon}\left(R^{\epsilon} - 1\right)}{\frac{d}{d\epsilon}\epsilon}\right]$ $\displaystyle =\lim_{\epsilon \to 0} \left[\frac{R^{\epsilon}\ln R}{1}\right]$ $\displaystyle =\ln R \lim_{\epsilon \to 0} \left[R^{\epsilon}\right]$ $\displaystyle =\ln R\!$

The solution to the equation

$\displaystyle \frac{d n_i(t)}{dt} = n_i(t) \ln R$
is
$\displaystyle n_i(t) = n_i(0) e^{t\ln R} = n_i(0) R^{t}.\!$
Note that the continuous case and the original discrete-generation case agree for all values of $\displaystyle t$ . We can define the instantaneous growth rate $\displaystyle r = \ln R$ for convenience.

## Continuous rate of change

If two organisms grow at different rates, how do their proportions in the population change over time?

Let $\displaystyle r_1$ and $\displaystyle r_2$ be the instantaneous rates of increase of type 1 and type 2, respectively. Then

$\displaystyle {dn_i(t) \over dt} = r_i n_i(t).$
With the total population size
$\displaystyle n(t) = n_1(t) + n_2(t)\!$
we have the proportion of type 1
$\displaystyle p(t) = {n_1(t) \over n(t)}$
$\displaystyle s \equiv s_{12} = r_1 - r_2\!$
Given our interest in understanding the change in gene frequencies, our goal is to compute the rate of change of $\displaystyle p(t)$ .
 $\displaystyle {\partial p(t) \over \partial t}$ $\displaystyle = {\partial \over \partial t}\left({n_1(t) \over n(t)}\right)$ $\displaystyle = {\partial n_1(t) \over \partial t}\left({1 \over n(t)}\right) + n_1(t){-1 \over n(t)^2}{\partial n(t) \over \partial t}$ $\displaystyle = {\partial n_1(t) \over \partial t}\left({1 \over n(t)}\right) + n_1(t){-1 \over n(t)^2}\left({\partial n_1(t) \over \partial t} + {\partial n_2(t) \over \partial t}\right)$ $\displaystyle = {r_1 n_1(t) \over n(t)} - {n_1(t) \over n(t)^2}\left(r_1 n_1(t) + r_2 n_2(t)\right)$ $\displaystyle = {r_1 n_1(t) \over n(t)} - {n_1(t) \over n(t)^2}\left(r_1 n_1(t) + (r_1-s)(n(t)-n_1(t))\right)$ $\displaystyle = {r_1 n_1(t) \over n(t)} - {n_1(t) \over n(t)^2}\left(r_1 n(t) -s n(t) + s n_1(t))\right)$ $\displaystyle = {n_1(t) \over n(t)^2}\left(s n(t) - s n_1(t))\right)$ $\displaystyle = s{n_1(t) \over n(t)}\left(1 - {n_1(t) \over n(t)}\right)$ $\displaystyle = s p(t)(1-p(t))\!$
The logit function $\displaystyle \mathrm{logit} (p) = \ln {p \over 1-p}$ , which takes $\displaystyle p \in [0,1] \to \mathbb{R}$ , induces a more natural space for considering changes in frequencies. In logit terms,